A comparative study of launch canister thermal control systems using a liquid or gas working medium. (25th February 2018) - Zhang, Qiang; Ye, Hong; Wang, Zijun
Highlights: A thermal control system using a liquid working medium (L-TCS) in launch canister is proposed. The thermal control systems using a gas or liquid working medium are compared. The comparison is based on the same working medium's heat capacity flow rate. The L-TCS is better in both energy efficiencies and temperature control effects. Abstract: A launch canister thermal control system (TCS) is important for the protection of the engine of a rocket and its electronic devices. Current TCSs using a gas working medium (G-TCS) have high energy consumption and unsatisfactory temperature control effects. Hence, in this study, a TCS using a liquid working medium (L-TCS) was proposed. The two systems were compared through verified simulation models and engineering calculations in different cases. The results of the loaded stable operation case showed that an L-TCS requires much less energy and has a much higher energy efficiency in all the analyzed seasons, namely, spring, summer, and winter, in comparison to the G-TCS. Moreover, an L-TCS is superior to a G-TCS in terms of the temperature control effects. In the unloaded start-up case, both the TCS types have their respective advantages, but their start-up durations are long. However, introducing a mixing fan can drastically decrease the start-up duration of the L-TCS.